Squamous Cell Carcinoma Bartholin’s Gland: Management Challenges: Case Report and Review of Literature - Verma, Pallavi; Chawla, Sushil; -, Sandhyarani; Anand, Sunil; Mahajan, Rahul; Shelly, Divya (Asian Pacific Journal of Cancer Care, 2025)
Bartholin gland carcinoma is an unusual malignancy, accounting for less than 5% of all vulval cancers. Squamous cell carcinoma is the most common histological type, followed by adenocarcinoma. Bartholin’s gland carcinomas develop into masses of varying sizes and may be ulcerated or deep to the surface with the overlying skin intact. Because little is known about bartholin’s gland cancer, it is frequently misdiagnosed as an abscess or a cyst. Diagnosis is often delayed until discovered at advanced stages. To add to the literature, we report a case of locally advanced stage bartholin’s gland carcinoma in a postmenopausal lady, who is managed with radical partial vulvectomy with bilateral inguinofemoral lymphadenectomy with vulvar-vaginal reconstruction by gracilis myocutaneous flap followed by adjuvant concurrent chemoradiation. We aim to create awareness among clinicians and provide new insights for the diagnosis and treatment of this rare malignancy.